DESIGN AND EVALUATION OF NEOMYCIN SULFATE-LOADED SOLID LIPID NANOPARTICLES (SLNs) FOR OCULAR ADMINISTRATION - SHETTY, VEEKSHA S.; DS, SANDEEP (International Journal of Applied Pharmaceutics, 2025)
Objective: The current study aimed to formulate and evaluate solid lipid nanoparticles (SLNs) loaded with Neomycin Sulfate for ocular administration for the management of bacterial conjunctivitis. Methods: The formulation of Neomycin Sulfate-loaded SLNs was carried out using the solvent evaporation and ultrasonication methods. Optimization of SLNs was performed using a 32 full factorial statistical design, and the optimized batch of SLNs was evaluated for various parameters. Results: The optimized formulation exhibited a mean particle size of 178.2±2.23 nm with an entrapment efficiency of 85.6%, which was in good agreement with the predicted values obtained using Design Expert software. The formulation revealed a sustained drug release pattern with a maximum drug release of 82.11±0.34% lasting 8 h with Higuchi's drug release kinetics mechanism. The Hen’s egg test-Chorioallantoic membrane (HET-CAM) assay revealed that the optimized formulation was non-irritating and non-toxic for ocular use. Additionally, histopathological analysis showed no structural damage to the cornea, confirming the formulation’s safety for ocular administration. Short-term stability studies on the optimized formulation demonstrated that it remained stable, with no notable changes in the assessed parameters over 3 mo. Conclusion: From the above outcomes of the study results, we conclude that Neomycin sulfate-loaded SLNs could be a potential drug delivery approach for the treatment of bacterial conjunctivitis in the eye.